Exploring the Societal Implications of Accounting Practices and Standards - Kurniawan, Bayu (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This research explores the societal impacts of accounting practices and standards on economic decision-making, corporate governance, and technological advancements. Research Design and Methodology: Employing a qualitative approach, the study systematically reviews and conducts a thematic analysis of the literature focusing on transparency, accuracy, and reliability in financial reporting. Findings and Discussion: The findings highlight regulatory measures, such as the Sarbanes-Oxley Act, that enhance corporate governance accountability. Technological innovations, such as blockchain and AI, improve efficiency but raise significant ethical and security concerns. Implications: The study underscores the importance of robust governance frameworks and effective cybersecurity measures for the responsible use of technology in accounting, offering valuable insights for policymakers and practitioners.